LncRNA SLCO4A1-AS1 facilitates growth and metastasis of colorectal cancer through β-catenin-dependent Wnt pathway - Jiangtao Yu; Zhiyang Han; Ziquan Sun; Yue Wang; Ming Zheng; Chunfang Song (Journal of Experimental & Clinical Cancer Research, 2018)
Abstract Background Emerging evidence has shown long noncoding RNAs (lncRNAs) exert important roles in colorectal cancer (CRC) tumorigenesis. However, most lncRNAs involved in this process remain undefined and the underlying molecular mechanisms mediated by lncRNAs are largely unknown. Methods An unbiased screening was used to identify novel lncRNAs involved in CRC according to an online-available data dataset. In situ hybridization (ISH) and qRT-PCR was used to detect lncRNA expression patterns. CCK8, colony formation, fluorescence activated cell sorter (FACS), transwell, xenograft nude mouse model and western blot assays were used to analyze the functions of SLCO4A1-AS1. RNA-pulldown, western blot, RNA fluorescence in situ hybridization (RNA-FISH) and electrophoretic mobility shift assay (EMSA) assays were utilized to explore the molecular mechanism of SLCO4A1-AS1. Results LncRNA SLCO4A1-AS1 was significantly upregulated in CRC tissues and its overexpression was closely related with poor prognosis and tumor metastasis. By knocking down SLCO4A1-AS1, we found that SLCO4A1-AS1 promoted the proliferation, migration, invasion and epithelial–mesenchymal transition (EMT) of CRC cells in vitro, as well as inhibited cell apoptosis. Moreover, SLCO4A1-AS1 dramatically delayed tumor propagation in vivo. Mechanistically, SLCO4A1-AS1 activates Wnt/β-catenin signaling. SLCO4A1-AS1 enhanced the stability of β-catenin by impairing the interaction of β-catenin with GSKβ and inhibiting its phosphorylation. Finally, restoration of β-catenin protein level rescued the proliferation, migration and invasion in SLCO4A1-AS1-depleted CRC cells. Conclusion SLCO4A1-AS1 serves as an oncogenic role in CRC through activating Wnt/β-catenin signaling pathway. And SLCO4A1-AS1 might be a useful biomarker for CRC diagnosis and prognosis.